Penerapan Model Inkuiri untuk Meningkatkan Kemampuan Membaca Pemahaman pada Materi Teks Narasi Sejarah Siswa Kelas VB UPTD SD Inpres Naikoten 2 Kota Kupang - Wonjal, Melania; Sampe, Markus; Nawa, Netty E. A. (Lembaga Yasin AlSys, 2025)
Reading comprehension is an essential skill in learning, yet it remains a challenge for Class VB students at SD Inpres Naikoten 2 Kota Kupang, as evidenced by observational data indicating low achievement in reading comprehension tests. This study aims to improve students’ reading comprehension skills on historical narrative texts through the implementation of the inquiry-based learning model. The research employed a Classroom Action Research (Penelitian Tindakan Kelas) approach conducted in two cycles, with data collected through observation, tests, and document analysis. The results showed that the application of the inquiry model significantly enhanced students’ reading comprehension, as demonstrated by an increase in mastery learning from 16.67% in the pre-cycle to 55.56% in the first cycle and 88.89% in the second cycle. Additionally, the average student score improved from 65.22 to 84.78, accompanied by increased teacher activity and student engagement during the learning process. These findings suggest that the inquiry-based learning model is effective and can serve as a strategic alternative to enhance reading comprehension among elementary school students.